Contributions of Marine Cluster for Regional Sustainability: Economic Prospective for Azores - Paramio, Luz (2013)
The project SEAValue proposes to develop a first integrate approach to valuation of the Sea of Azores from economic view analyses.The project aims the estimation of the contribution of the sea, namely, maritime sector and marine ecosystem services, and their benefits for the sustainable development of the Autonomous Region of Azores through a responsive and effective decision support process.Nowadays, the world context of the sustainable ocean governance is one of the paradigms that the Azores Autonomous Region should address, in particular, due to the geographical position in the core of the Atlantic area and its geopolitical implicit factors. The extension of the Portuguese EEZ would raise new challenges and responsibilities to sea management. Different governance transversal issues as legal, planning, conservation, economic and their scales of articulation into local, national, European and international level, need a coherent governance framework. Estimate the value, specially the economic value, bring the awareness of the benefits that sea offers to Azores. Furthermore it would enhance the decision support process through define of strategic options for the development of public policy of the Region. The multidisciplinary research of the project from Governance, Economy and Environmental Planning approach provides integrate and holistic vision of the Sea and would project outputs as tools and options for operational decisions.